Lived experiences of negative symptoms in first‐episode psychosis: A qualitative secondary analysis. Issue 4 (24th March 2018) - Gee, Brioney; Hodgekins, Jo; Lavis, Anna; Notley, Caitlin; Birchwood, Max; Everard, Linda; Freemantle, Nick; Jones, Peter B.; Singh, Swaran P.; Amos, Tim; Marshall, Max; Sharma, Vimal; et al.
Abstract : Aim: Exploring how negative symptoms are experienced and understood by individuals with lived experience of psychosis has the potential to offer insights into the complex psychosocial processes underlying negative symptom presentations. The aim of the current study was to investigate lived experiences of negative symptoms through secondary analysis of interviews conducted with individuals recovering from first‐episode psychosis. Method: Transcripts of in‐depth interviews with participants ( n = 24) recruited from Early Intervention in Psychosis services were analysed thematically with a focus on participants' experiences and personal understandings of features corresponding to the negative symptoms construct. Results: Descriptions of reductions in expression, motivation and sociability were common features of participants' accounts. Several participants described the experience of having difficulty interacting as like being a "zombie". Some participants experienced diminished capacity for emotion, thought or drive as underlying these experiences. However, participants typically attributed reductions in expression, motivation and sociability to medication side‐effects, lack of confidence or active avoidance intended to protect them from rejection or ridicule, sometimes linked to internalized stigma. Conclusions: Personal accounts of experiences of reduced expression, motivation and sociability during first‐episode psychosis highlight the personal meaningfulness and role of agency in these features, challenging the framing of negative symptoms as passive manifestations of diminished capacity.